Preparation and characterization of activated carbon from grape stalk by zinc chloride activation - Ozdemir, Isilay; Sahin, Mehmet; Orhan, Ramazan; Erdem, Mehmet (Elsevier Science Bv, 2014)
In this study, low cost activated carbon was prepared from the grape stalk by chemical activation with ZnCl2 in CO2 atmosphere and its characteristics were determined. Experiments were carried out at different carbonization temperature and time, impregnation time and impregnation ratio, which had significant effect on the pore structure and surface area of carbon. The prepared activated carbon was characterized by proximate-ultimate analysis, BET surface area, iodine number, surface functional group analysis by Boehm's titration and FT-IR analysis, pHzpc, SEM-EDX and particle size distribution. Results showed that the carbonization temperature and impregnation ratio have significant effect on the surface area and pore structure of the prepared activated carbon. The optimum conditions for preparing the activated carbon having the highest surface area were found to be a carbonization temperature of 700 degrees C, carbonization time of 120 min, impregnation time of 36 h and ZnCl2/grape stalk ratio of 2. The results showed that the BET surface area, total pore volume, iodine number, pHzpc and the yield of activated carbon prepared under the optimum conditions were 1411 m(2)/g, 0.723 cm(3)/g, 1760 mg/g, 2.84 and 26.48%, respectively, and the activated carbon has acidic surface functional groups and highly porous surface with cracks, channels and large holes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Activated carbon; Grape stalk; Activation; Zinc chloride; Surface chemistry